Ex malo, bonum? Dilemmas (and Opportunities) as a result of Dobbs (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
This contribution aims to retrace the fundamental stages of the complex and critical jurisprudential affirmation of the right to voluntary termination of pregnancy in the US experience, trying to synthetically highlight at least three elements: (a) the political-social difficulty that there is today in the search for a new political-juridical balance to be established at the federal level; (b) the path of the ‘defederalization’ of rights as an always helpful tool for posing crucial questions to the people in a federal state; finally (c) highlight the potential opportunities offered by the Dobbs v. Jackson Women’s Health Organization of 2022 ruling to reduce social-political polarization and confrontation.
Keywords: Abortion; United States Supreme Court; Jurisprudence; Women’s Rights; Reproduction